The Influence of BIC Interest Rates, Money Supply, and Political Connection on the LQ45 Stock Price Index - Nala Ratih; Avininda Dewi Nindiasari (IECON: International Economics and Business Conference, 2025)
This study aims to analyze. the. influe.nce. of SBI inte.re.st rate.s, the. mone.y supply, and political conne.ctions on the. LQ45 stock price. inde.x. The. approach use.d in this study is de.scriptive. quantitative. with data colle.ction te.chnique.s be.ing se.condary data in the. form of time. se.rie.s, name.ly data obtaine.d from the. Bank Indone.sia (BI) and Indone.sia Stock E.xchange. (IDX) we.bsite.s for the. pe.riod 2019-2023. The. de.te.rmination of the. sample. se.le.ction use.d in this study is the. purposive. sampling te.chnique.. The. analysis me.thod use.d is Pane.l Data Re.gre.ssion Analysis by conducting the. Chow te.st, Hausman te.st, Lagrange. Multiplie.r (LM) te.st, Classical Assumption te.st, t-te.st, F-te.st, and Coe.fficie.nt of De.te.rmination te.st. The. e.ntire. data proce.ssing of the. re.se.arch will be. conducte.d with the. he.lp of a compute.r using the. Microsoft E.-Vie.ws 13 application. The. re.se.arch re.sults show that the. BIC inte.re.st rate. has a significance. value. of 0.7758 > 0.05 with a t-statistic value. of 2.406805, thus it can be. conclude.d that the. BI inte.re.st rate. doe.s not have. a significant e.ffe.ct on the. LQ45 stock price. inde.x (H1 is re.je.cte.d). The. influe.nce. of the. mone.y supply on the. stock price. inde.x yie.lds a significance. value. of 0.0360 < 0.05 with a t-statistic value. of -2.240280, thus it can be. conclude.d that the. mone.y supply doe.s not have. a positive. but significant e.ffe.ct on the. LQ45 stock price. inde.x (H2 is re.je.cte.d). The. influe.nce. of political conne.ction on the. stock price. inde.x yie.lds a significance. value. of 0.0917 > 0.05 with a t-statistic value. of -1.767619, thus it can be. conclude.d that political conne.ction doe.s not have. a positive. and significant e.ffe.ct on the. LQ45 stock price. inde.x (H3 is re.je.cte.d).